Characterization and Concentration Prediction of Dust Pollution in Open-Pit Coal Mines - Guilin Wang; Wei Zhou; Zhiming Wang; Xiang Lu; Yirong Zhang (Atmosphere)
Dust pollution is a major problem formed caused by opencast coal mining, and its prevention is a key prerequisite for the realization of green and climate-friendly mining in open-pit coal mines. In this paper, we conducted the real-time monitoring of dust concentration and meteorological parameter data in different areas of a large-scale open-pit coal mine in China and used multivariate statistical analysis to study the characteristics of the variation in dust concentration and its influencing factors in operating and non-operating areas. The results showed that there was a significant correlation between TSP, PM10, and PM2.5 in the same area. There was a significant difference in the percentage of PM2.5/PM10 between the operation area and the non-operation area, with particles in the range of 2.5–10 μm dominating close to the operation area and particles in the range of 0–2.5 μm dominating away from the operation area. The production intensity had a greater effect on dust concentration in the operation area, and there was no significant relationship with dust concentration away from the operation area. Wind speed—wind force—wind direction, temperature, and humidity are all correlated with particulate matter. The LSTM model is more suitable for predicting the dust concentration in open-pit coal mines. The results of this study can provide a reference for dust prevention and control in open-pit coal mines.